Facial expression and the mask / Syazwani Abd Rahim, Ponirin Amin and Rafeah Legino - Abd Rahim, Syazwani; Amin, Ponirin; Legino, Rafeah (Research Innovation Business Unit, 2014)
This research is about the mask which is usually worn on the face, for protection, social environments and sometimes it is a part of decoration or craft in any performance, ceremonial and practical purposes. The mask functions as an expression which can be changed depending on the situation and place. The message of the expression will convey information directly to the audience or people around. This study focuses on multiple expressions, such as joy, sadness, fear, disgusts or contempt. Therefore the mask is also part of conservation piece to protect the original objects from disappearing. This study is to determine the types of facial expression from different masks, which were viewed and analysed then constructed into visual development according to the themes that have been identified with appropriate face expression character into installations sculpture artwork. Furthermore, this study focusses on alternative printmaking which differs from the traditional method. Making installations artwork depends on the creativity of the artists, idea and the ability to overcome technical problems. Artwork needs large space and form to be displayed, However, the idea of multiple print have been created for multiple copies of the same original object using casting technique. This technique originates from the use of ceramic such as POP (plaster of Paris) and slip. Creating the mould makes the object prominent and suitable to be transferred into installations elements either in a small or large space. The beauty of making artwork from alternative technique is the artists must be creative, be a good designer, full of knowledge in ceramic and brave or able to multitask to create the artwork. The audience must understand when they see this artwork because 3D work is actually a copy of the real original object and is applied into art pieces. The purpose of this study is to show the importance of expression in our daily life when facing different situations or being in different environments, the expression make humans move display different facets of life. Therefore, the impact from this artwork does not only reflect the audience but it also illustrates how the techno culture will support the masks pieces.